Review—Nanocomposite-Based Sensors for Voltammetric Detection of Hazardous Phenolic Pollutants in Water. Issue 3 (17th February 2020) - Patel, Bhargav R.; Noroozifar, Meissam; Kerman, Kagan
Abstract : Due to the close contingency between human health and their socio-economic well-being with regards to environmental pollution, environmental monitoring of various pollutants is global cause for concern. There is an urgent need for developing a sensing device that is capable for multiplex detections, cost-effective, rapid, sensitive, portable, and selective. With the advancement in the field of nanotechnology, nanocomposites are emerging as model modifier components for fulfilling the aforementioned needs and amplifying the electrochemical detection mechanisms. The interactions between the multiple components in the nanocomposite and their synergistic effects makes it superior and enhances the performance of the electrochemical sensor compared to when a singular nanomaterial component is used in the sensor. This review article apprises recent advances in the novel methodologies for fabrication of nanocomposites for voltammetric detection of water pollutants. The improved performance of the nanocomposite-based electrochemical sensors in detection of organic phenolic pollutants such as dihydroxybenzene isomers (DHB), bisphenol A (BPA) and 4-nitrophenol (4-NP) were highlighted. The future perspectives with challenges and strategic angles of development for the nanocomposite-based electrochemical sensors in environmental monitoring are also discussed.